Recent advancements to engineer mesenchymal stem cells and their extracellular vesicles for targeting and destroying tumors. (March 2023) - Karami Fath, Mohsen; Moayedi Banan, Zahra; Barati, Reza; Mohammadrezakhani, Omid; Ghaderi, Aliasghar; Hatami, Ali; Ghiabi, Shamim; Zeidi, Nazanin; Asgari, Katayoon; Payandeh, Zahra; Barati, Ghasem
Abstract: Mesenchymal stem cells (MSCs) have the ability to migrate into tumor sites and release growth factors to modulate the tumor microenvironment. MSC therapy have shown a dual role in cancers, promoting or inhibiting. However, MSCs could be used as a carrier of anticancer agents for targeted tumor therapy. Recent technical improvements also allow engineering MSCs to improve tumor-targeting properties, protect anticancer agents, and decrease the cytotoxicity of drugs. While some of MSC functions are mediated through their secretome, MSCs-derived extracellular vesicles (EVs) are also proposed as a possible viechle for cancer therapy. EVs allow efficient loading of anticancer agents and have an intrinsic ability to target tumor cells, making them suitable for targeted therapy of tumors. In addition, the specificity and selectivity of EVs to the tumor sites could be enhanced by surface modification. In this review, we addressed the current approaches used for engineering MSCs and EVs to effectively target tumor sites and deliver anticancer agents. Graphical abstract: Graphical abstract . Engineering MSCs and their EVs to target and destroy tumors. MSC: mesenchymal stem cell, EVs: Extracellular vesicles, miRNA: microRNA. Image 1